Потири з храмів м. Глухова у зібранні скарбниці Національного музею історії України - Березова, С.А.; Полідович, Ю.Б.; Удовиченко, І.В. (Сіверщина в історії України, 2023)
У статті йдеться про два срібні потири роботи київського майстра Івана Равича, які нині зберігаються в Скарбниці Національного музею історії України. Завдяки вкладним написам відомо, хто був замовником і до яких храмів робили вклади. Письмові джерела дозволяють дізнатися про долю людей, чиї імена викарбувані на витворах золотарства. Потир 1738 р. пов’язаний з іменем Христини Никифорівни, удови глухівського сотника Федора Омеляновича. За джерелами встановлюється цей старшинський рід – син Іван і онуки Григорій і Михайло Омеляновичі. Замовником потира 1749 р. був архімандрит Петропавлівського Глухівського монастиря Никифор Грибовський. Він був настоятелем обителі 18 років, був відомий як суворий керівник, відзначився своєю участю у громадському житті Гетьманщини. Наприкінці життя Грибовського перевели до Свято-Микільського Пустинного монастиря у Києві. This article is about two silver chalices, made by the Kyiv silversmith Ivan Ravych (master’s mark «IR»), which are now kept in the Treasury of the National Museum of the History of Ukraine. The inscriptions on the items reveal the names of the donators as well as the churches the chalices were gifted. Written sources help to find out about the life of people whose names are engraved on silversmith’s pieces. The chalice of 1738 (fig. 1–2) is connected with the name of Khrystyna Nykyforivna – the widow of Hlukhiv sotnyk Fedir Omelianovych. According to the sources, this family of elders is established – son Ivan and grandsons Hryhorii and Mykhailo Omelianovych. But this information still needs additional confirmation. The donator of the chalice made in 1749 (fig. 4–6) was Nykyfor Hrybovskyi, who was the archimandrite of the Peter and Paul Hlukhiv Monastery. He was the abbot of the monastery for 18 years, was known as a strict leader, distinguished himself by his participation in the public life of the Cossack Hetmanate. At the end of his life, Hrybovskyi was transferred to the St. Michael Monastery on the Slupa-river in Kyiv.